Surface crack growth in cylindrical hollow specimen subject to tension and torsion - V. Shlyannikov; R. Yarullin; R. Yarullin (Fracture and Structural Integrity)
The subject for studies is an aluminium cylindrical hollow specimen with external axial and part circumferential semi-elliptical surface crack undergoing fatigue loads. Both the optical microscope measurements and the crack opening displacement (COD) method are used to monitor and calculate both crack depth and crack length during the tests. The variation of crack growth behaviour is studied under cyclic axial tension, pure torsion and combined tension+torsion fatigue loading. For the particular surface flaw geometries considered, the elastic and plastic in-plane and out-of-plane constraint parameters, as well as the governing parameter for stress fields in the form of In-integral and plastic stress intensity factor, are obtained as a function of the aspect ratio, dimensionless crack length and crack depth. The combined effect of tension and torsion loading and initial surface flaw orientation on the crack growth for two type of aluminium alloys is made explicit. The experimental and numerical results of the present study provided the opportunity to explore the suggestion that fatigue crack propagation may be governed more strongly by the plastic stress intensity factor rather than the magnitude of the elastic SIFs alone. One advantage of the plastic SIF is its sensitivity to combined loading due to accounting for the plastic properties of the material.